Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1152/ajpregu.00734.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role for pituitary adenylate cyclase activating polypeptide in cystitis-induced plasticity of micturition reflexes

Abstract: Pituitary adenylate cyclase activating polypeptide (PACAP) peptides are expressed and regulated in sensory afferents of the micturition pathway. Although these studies have implicated PACAP in bladder control, the physiological significance of these observations has not been firmly established. To clarify these issues, the roles of PACAP and PACAP signaling in micturition and cystitis were examined in receptor characterization and physiological assays. PACAP receptors were identified in various tissues of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
119
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 60 publications
(130 citation statements)
references
References 76 publications
11
119
0
Order By: Relevance
“…We have confirmed that the CRF IR in the lateral horn of L 6 -S 1 is associated with the autonomic nucleus by using segmentation protocols previously used and validated (6,61,64) and by also staining spinal cord sections for nNOS IR (48), a marker for preganglionic autonomic neurons (Fig. 4C).…”
Section: Crf Expression In Lumbosacral Spnsupporting
confidence: 71%
See 3 more Smart Citations
“…We have confirmed that the CRF IR in the lateral horn of L 6 -S 1 is associated with the autonomic nucleus by using segmentation protocols previously used and validated (6,61,64) and by also staining spinal cord sections for nNOS IR (48), a marker for preganglionic autonomic neurons (Fig. 4C).…”
Section: Crf Expression In Lumbosacral Spnsupporting
confidence: 71%
“…Previous studies have demonstrated that a number of neurotrophic factors (15,59), neuropeptides (6,57), and cytokines (27,67) are upregulated in the urinary bladder after CYPinduced cystitis. Subtractive techniques to block these factors improve bladder function and reduce pain-related behaviors (6, (A and B) or nerve fibers in the suburothelial plexus in whole mount preparations of the urothelium/suburothelium (C and D) in control (A and C) or CYP-treated (B and D) rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Greater basal activity in the primary bladder afferents in the DRG or in the target organ itself (i.e., urinary bladder) could result in increased pCREB expression in the absence of inflammation by increasing Ca ++ and/or cAMP in VIP −/− mice. Primary afferent cells in the DRG express VIP (Morgan et al, 1999;Hernandez et al, 2006) and VIP receptors (Yashpal et al, 1991;Braas et al, 2006). Thus, absence of VIP in the VIP −/− mice could produce a direct effect on primary afferent cells.…”
Section: Vip −/− Mice Exhibit Higher Basal Level Of P-creb-ir In Drgmentioning
confidence: 99%